Correlation of the Neck Circumference with Blood Pressure - Makaju, Sarbada; Chaudhary, Sonam; Alam, Munna (Journal of College of Medical Sciences-Nepal, 2018)
Background: The growing epidemic of hypertension owing to physical inactivity and dietary modification is a global burden. The obesity which acts as a pre-disposing factor for blood pressure can be measured with neck circumference (NC) as well. Thus, the aim of this study is to find out the relation between the components of blood pressure and the neck circumference. Materials and Methods: The study was conducted on 1000 Nepalese individuals in Manipal Teaching Hospital, Manipal College of Medical Sciences and surrounding locality after getting the ethical clearance. The age range for participants were between 30-60 years from both genders. The systolic and diastolic components of blood pressure (SBP, DBP) with and without the history of anti-hypertensive medication and the neck circumferences of the participants were taken in consideration. The data were analyzed with SPSS 20 version. Results: The male occupied 76.4% and the rest were female. The total mean of SBP and DBP were comparatively more in male [123.24±11.11mmHg; 83.08±8.24mmHg] than in female. The maximum numbers of participants taking anti hypertensive drugs [AHD] in male and female were age range between 35-44 and 45-54 respectively. The total mean of NC is more in male (38.08±2.46 cm) than in female. The NC had weak positive correlation with SBP and DBP. This correlation was more positive with DBP in female participants under medication which was statistically significant (p<0.05). Conclusions: The NC shows the positive correlation with the components of blood pressure. This correlation is comparatively more with DBP in female taking anti-hypertensive drugs.